PENERAPAN ALAT BUKTI DALAM TINDAK PIDANA INFORMASI DAN TRANSAKSI ELEKTRONIK - Malisya Putri (UM.Tapanuli Selatan, 2024)
Along with the increasingly rapid development of communication via the internet, various crimes have also emerged that are committed using the internet medium. It cannot be denied that the use of the sophisticated and fast internet has also given rise to very sophisticated crimes and it is difficult to identify the perpetrators. This is because the internet is an invisible (virtual) communication medium, so that criminals can easily remove traces without being clearly identified. The research method used is empirical normative legal research. The research results show that the process of implementing evidence for ITE crimes begins with an inquiry and investigation process, then the electronic evidence will be examined through a digital forensics stage process, namely; Acquisition; Examination and analysis, and Documentation and presentation.